2016
DOI: 10.1177/0363546515621541
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Tibia Fixation of Soft Tissue Grafts in Anterior Cruciate Ligament Reconstruction

Abstract: PROSPERO International Prospective Register of Systematic Reviews No. 42014015464.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 49 publications
5
33
1
Order By: Relevance
“…Primary stability of aperture fixation in this group was equal to primary ACL-R (n.s.) and correspondingly did not differ from primary stability of native ACL-R found in the literature [16,19,21,22].…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Primary stability of aperture fixation in this group was equal to primary ACL-R (n.s.) and correspondingly did not differ from primary stability of native ACL-R found in the literature [16,19,21,22].…”
Section: Discussionsupporting
confidence: 44%
“…Primary stability of tibial of soft tissue graft fixation with an IFS has been assessed in several biomechanical studies; ultimate strength has shown to be between 360 and 1200 N in biomechanical testing, with graft slippage between the IFS and the bony tunnel being the typical mode of failure [16][17][18][19][20][21]. Maximum load of IFS fixation has proven to be dependent on bone density, screw length and ratio of screw-tunnel-diameter [16][17][18][19][20][21]. Furthermore, it has been shown that primary stability of tibial IFS fixation is inferior in the revision setting after ACL-R, when a preexisting semi-anatomical tunnel or a tibial tunnel widening is present [16].…”
Section: Discussionmentioning
confidence: 99%
“…No matter what the graft choice was, double fixation was routinely considered on both sides of the joint to improve fixation strength and increase stiffness of the construct. 6,10,31,42…”
Section: Discussionmentioning
confidence: 99%
“…Presence of osteoporosis or osteopenia will interfere with the interference screw fixation, which may be mediated with cortical button fixation to strong cortical bone. 2,10 Although no FHL transfer failures have been reported in the literature, the cortical button augmentation hold potential to enhance postoperative success. 16 Bone mineral density has been reported with mixed results to affect tendon transfer in the foot and ankle.…”
Section: Discussionmentioning
confidence: 99%